The education of Henry Adams - Adams, Henry (Oxford Oxford University Press, 1999)
The great-grandson of President John Adams and the grandson of President John Quincy Adams, Henry Adams possessed one of the most remarkable minds of his generation. Yet he believed himself fundamentally unsuited to the era in which he lived?the tumultuous period between the Civil War and World War I.
Includes index
Keywords: Henry Adams